DUALISME PERATURAN TENTANG PENGAWASAN TERHADAP ADVOKAT DI INDONESIA - Anette Eka Permata Putri (2022)
Advocate is a noble profession that provides assistance to justice seekers. Related arrangements are regulated through Law No. 18 of 2003 and the Advocate's Code of Ethics. However, in both regulations there are inconsistent articles regarding the supervision of advocates. The purpose of this research is to find out how to resolve the different rules regarding the supervision of advocates based on Law No. 18 of 2003 and the Code of Ethics of the Association of Indonesian Advocates Congress. This research is a normative juridical research that examines regulations related to the supervision of advocates. The data obtained in this study were sourced from literature studies and interviews. The collected data was then analyzed prescriptively. The results of this study are the Lex Specialist derogate Lex Generalis principle cannot be used in this case so that what can be used is the Lex Superior derogate Legi Inferiori principle because in this principle the highest law can ignore laws with lower status so that the code of ethics itself does not have a position in Law No. 12 of 2011, then advocates should be more subject to the existing laws and regulations